Midya bandido a critical discourse analysis on Imbestigador, a program of power - Mesalucha, Sadeka Sarra Fabillar 1990- (2014)
"Both the AGB Nielsen and Kantar TNS for few consecutive years now have named couple of investigative programs as among the top 10 watched programs at least in Mega Manila households. From this consistent position of investigative programs in the ranks of most watched, the researcher chose one program among the investigative shows that the AGB Nielsen and Kantar TNS were able to include in the top list. The researcher selected GMA-7's Imbestigador as the primary unit of analysis of power and its normalization to examine the program's theme and narrative. Also, Althusser's theories of Repressive State Apparatus and Ideological State Apparatus plus the phenomenon of interpellation were also utilized. The researcher used textual analysis to map power on program's snippets. The history of the discipline that Imbestigador belongs to was also presented. The researcher conducted interview to the executive producer, associate producer and researcher of Imbestigador. As a result of this study, it turned out that Imbestigador's format and narrative are patterned to the old but thriving juridical conception of power that mostly sets a negative yet powerful impression of power."